Sterilization of Medical 3d Printed Plastics: Is H2O2 Vapour Suitable? - Sosnowski, E. P.; Morrison, J. (CMBES Proceedings, 2017)
3D printers that precisely fuse plastic filament are enabling the medical device manufacturing sector to produce high-quality plastic medical devices and implants. However, the low-temperature fusing process implies that post-production sterilization must also occur at a low temperature or destroy the precision of the product. This study characterizes the effects of hydrogen peroxide (H 2 O 2 ) vapour sterilization on ASTM-compliant 3D printed tensile samples of polylactic acid (PLA), polycaprolactone (PCL), and polycarbonate (PC). The sterilization process caused physical deformations in PCL. Additionally, increases were observed in PCL and PC sample thickness, and in PC sample width. Decreases in Young’s Modulus (E) were found in all three materials, while UTS decreased in PC, and strain at UTS increased in PCL. The findings demonstrate that the 3D printed materials can be compatible with H 2 O 2 vapour sterilization, but products must be designed to accommodate for changes that occur due to sterilization.